Sensitivity and Specificity of Urinalysis to Diagnose Urinary Tract Infection (UTI) in Patients with Urolithiasis at RSUP Dr. Sardjito Hospital - Purnomo, Awang Dyan; Tranggono, Untung (Indonesian Urological Association, 2016)
Objective: Urolithiasis could be caused by urinary tract infection (UTI). UTI in patients with urolithiasis need to be diagnose and manage as soon as possible. This study was aim to determine the diagnostic value of urinalysis examination to diagnose urinary tract infection (UTI) in patients with urolithiasis.Material & method: This study was an observational analytic with cross sectional study design, comparing one diagnostic tool with the gold standard tool to diagnose UTI. Total samples collected were 186 patients at Sardjito General Hospital, Yogyakarta. Urine culture and urinalysis were performed in patients with urinalysis and UTI. The results of urine culture and urinalysis were then compared by 2x2 table.Results: The sensitivity results on leukocyte esterase, eritrocyturia, bacteriuria, and nitrite respectively were 82.7%, 57.14%, 37.59%, and 13.53%. The specificity results on nitrite, bacteriuria, eritrocyturia, and leukocyte esterase respectively were 63.26%, 56.60%, 50.94%, and 33.96%. The highest level of accuracy was leukocyte esterase with 68.81% accuracy.Conclusion: This study showed that leukocyte esterase had good sensitivity with an accuracy of 68.81%. Examination of nitrite had the highest specificity compared to the other variables in urinalysis examination.